Characterization of Citrus sinensis transcription factors closely associated with the non-host response to Xanthomonas campestris pv. vesicatoria - Daurelio, Lucas Damian (2013)
Summary Plants, when exposed to certain pathogens, may display a form of genotype-independent resistance, known as non-host response. In this study, the response of Citrus sinensis (sweet orange) leaves to Xanthomonas campestris pv. vesicatoria (Xcv), a pepper and tomato pathogenic bacterium, was analyzed through biochemical assays and cDNA microarray hybridization and compared with Asiatic citrus canker infection caused by Xanthomonas citri subsp. citri. Citrus leaves exposed to the non-host bacterium Xcv showed hypersensitive response (HR) symptoms (cell death), a defense mechanism common in plants but poorly understood in citrus. The HR response was accompanied by differentially expressed genes that are associated with biotic stress and cell death. Moreover, 58 transcription factors (TFs) were differentially regulated by Xcv in citrus leaves, including 26 TFs from the stress-associated families AP2-EREBP, bZip, Myb and WRKY. Remarkably, in silico analysis of the distribution of expressed sequence tags revealed that 10 of the 58 TFs, belonging to C2C2-GATA, C2H2, CCAAT, HSF, NAC and WRKY gene families, were specifically over-represented in citrus stress cDNA libraries. This study identified candidate TF genes for the regulation of key steps during the citrus non-host HR. Furthermore, these TFs might be useful in future strategies of molecular breeding for citrus disease resistance.